2004
DOI: 10.1007/s00221-003-1737-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of decoding to analyze the contribution to the information of the correlations between the firing of simultaneously recorded neurons

Abstract: A new decoding method is described that enables the information that is encoded by simultaneously recorded neurons to be measured. The algorithm measures the information that is contained not only in the number of spikes from each neuron, but also in the cross-correlations between the neuronal firing including stimulus-dependent synchronization effects. The approach enables the effects of interactions between the 'signal' and 'noise' correlations to be identified and measured, as well as those from stimulus-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…The maximum number of neurons used was 28. The smooth and sublinear performance increase when adding neurons reveals information redundancy within the ensembles in this simple task (Franco et al, 2004) and supports the idea of distributed processing in the somatosensory cortex (Nicolelis et al, 1998;Ghazanfar et al, 2000). into the temporal precision of the somatosensory code.…”
Section: Error Analysissupporting
confidence: 74%
See 2 more Smart Citations
“…The maximum number of neurons used was 28. The smooth and sublinear performance increase when adding neurons reveals information redundancy within the ensembles in this simple task (Franco et al, 2004) and supports the idea of distributed processing in the somatosensory cortex (Nicolelis et al, 1998;Ghazanfar et al, 2000). into the temporal precision of the somatosensory code.…”
Section: Error Analysissupporting
confidence: 74%
“…However, previous studies in the whisker cortex suggested that these correlations play minor roles in the somatosensory code (Ghazanfar et al, 2000;Petersen et al, 2001) and that stimulusdependent changes in correlation convey almost no information about stimulus location , which allows a decoder that neglects correlation to extract virtually 100% of the encoded information . Nevertheless, the redundancy we found in ensembles of neurons, as revealed by the sublinear increase of information as the number of neurons increased (Franco et al, 2004), does reflect correlation between neurons as absence of "information independence" (Schneidman et al, 2003) and can be related to the "signal similarity" described in the whisker cortex Pola et al, 2003). Importantly, information theoretic redundancy should be carefully interpreted within the specific boundaries of the experiment, because it could reflect low entropy of the stimulus set chosen (Rolls et al, 1997) rather than actual redundancy in the somatosensory code.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…[Consistently, Gawne and Richmond (1993) showed that even adjacent pairs of neurons recorded simultaneously from the same electrode carried information that was approximately 80% independent.] In the research described by Panzeri et al (1999b), Rolls et al (2003b), and Franco et al (2004), we developed methods for measuring the information in the relative time of fi ring of simultaneously recorded neurons, which might be signifi cant if the neurons became synchronized to some but not other stimuli in a set, as postulated by Singer (1999). We found that for the set of cells currently available, almost all the information was available in the fi ring rates of the cells, and very little (not more than approximately 5% of the total information) was available about these static images in the relative time of fi ring of different simultaneously recorded neurons Panzeri et al 1999b;Rolls et al 2003bRolls et al , 2004.…”
Section: Y2mentioning
confidence: 99%
“…Thus, at least where objects are represented in the visual, olfactory, and taste systems (e.g., individual faces, odors, and tastes), information can be read out without taking into account any aspects of the possible temporal synchronization between neurons, or temporal encoding within a spike train Franco et al 2004;Panzeri et al 1999b;Rolls et al 1997aRolls et al , 2003bRolls et al , 2004Tovee et al 1993). …”
Section: Exponentially High Coding Capacitymentioning
confidence: 99%